Advances in non-small cell lung cancer mechanomedicine: deciphering the signaling networks that govern tumor-TME interactions - Antonios N. Gargalionis; Kostas A. Papavassiliou; Efthimia K. Basdra; Athanasios G. Papavassiliou (Journal of Experimental & Clinical Cancer Research)
Abstract Cells from the tumor microenvironment (TME) interact with tumor cells in non-small cell lung cancer (NSCLC) to form a reciprocal crosstalk which influences tumor growth, proliferation, metastasis and multidrug response. This crosstalk is modulated by TME mechanical inputs, which elicit the processes of mechanosensing and mechanotransduction. Recent advances in unveiling these signaling networks establish the interdisciplinary field of mechanomedicine to exploit emerging diagnostic, predictive and therapeutic tools for more effective NSCLC treatments.